The Genetic Organisation and Control of Putative Dehalogenase Gene Expression in Bacillus megaterium WSH-002: Putative Dehalogenase Gene Expression in Bacillus megaterium - Luqman Arif Zulkarnain; Fahrul Huyop (Journal of Tropical Life Science, 2023)
Dehalogenase-producing bacterium has been extensively studied due to their ability to reduce pollution in the environment. A previous study reported that Bacillus megaterium WSH-002 contains a putative haloacid dehalogenase type II gene, therefore, the presence of other genes associated with the dehalogenase regulatory gene function and uptake of halogenated compounds are expected. In the Bacillus megaterium WSH-002 whole genome, type II dehalogenase (DehWSH002) and two other genes related to dehalogenase regulatory and haloacid uptake genes were identified suggesting its ability to control the expression of putative dehalogenase(s) and the uptake of halogenated compounds into the cells. The phylogenetic analysis showed that DehWSH002 shared common features with DehLBHS1 of Bacillus megaterium strain BHS1 and Had protein of Bacillus megaterium strain ATCC12872/QMB1551. The study concluded that the genome of Bacillus megaterium WSH-002 contains a dehalogenase gene designated as dehWSH002 that is useful for biodegradation. In addition, further investigation of the adjacent genes suggested the presence of dehalogenase regulatory gene (dehR) and an uptake gene (dehP) in a single genetic organisation.